Effects of Different Seeds Pretreatments on the Germination of Five Local Trees: Four From The Fabaceae Family and One From the Bombacacea - Barthelemy, Yélemou; Abdoulaye, Tyano; Jonas, Koala; Rebecca, Zongo Rebecca (European Scientific Journal, ESJ, 2021)
The problem of the effectiveness of the established pre-treatments of seeds of local tree species is posed more and more often, with acuity. It appears necessary that studies are led to explore new methods of pre-treatment, or to update the old instructions applied, for a better success and at lower cost, of the production of seedlings. The present study concerned five species: Acacia nilotica, Adansonia digitata, Parkia biglobosa, Piliostigma reticulatum and Tamarindus indica. The methodology involved subjecting the seeds to three different pretreatments: (i) seeds treated with sulfuric acid (T0), (ii) seeds soaked in hot water for 24 hours (T1), (iii) seeds soaked in hot water for 48 hours (T2). For Acacia nilotica seeds, the different pretreatments did not result in statistically different germination rates. The germination rates are 77%, 65% and 62% (respectively for soaking in hot water for 48 hours, sulfuric acid and soaking in hot water for 24 hours). The different pretreatments also do not result in different germination rates for Tamarindus indica. Indeed, the germination rates after 30 days for this species are good but statistically identical (85% for the pretreatment with sulfuric acid and hot water for 24 hours). For Adansonia digitata, Parkia biglobosa and Piliostigma reticulatum, the sulfuric acid pretreatment gave the best germination rate (49%, 54% and 41% respectively). The results of this study may have practical consequences in terms of management of the different species studied. They show that immersing in boiling water and left for 24 hours and 48 hours yields fairly satisfactory germination rates for Acacia nilotica and Tamarindus indica seeds. These inexpensive techniques, accessible to all, can be considered as means to easily produce seedlings of these species.